2017
DOI: 10.4111/icu.2017.58.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change in prostate size after holmium laser enucleation: A prospective study

Abstract: PurposeTo analyze postoperative outcomes of prostate surgery, resected specimen weight is commonly used. The difference between the preoperative calculated transitional zone volume and actual enucleated specimen weight following holmium laser enucleation of the prostate (HoLEP) is reported at over 20%. The reason for this difference is unclear. We assessed the association of volume of the prostatic adenoma with enucleated weight, the volume and calculated volume of the adenoma by pre- and postoperative ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…HoLEP was carried out by a single surgeon (JSP), as described previously [ 8 , 9 ]. Briefly, we carried out enucleation that involved exposing the surgical capsule by incisions at the 5 and 7 o’clock positions just above the verumontanum, enucleating the median lobe, and then enucleating the lateral lobes.…”
Section: Methodsmentioning
confidence: 99%
“…HoLEP was carried out by a single surgeon (JSP), as described previously [ 8 , 9 ]. Briefly, we carried out enucleation that involved exposing the surgical capsule by incisions at the 5 and 7 o’clock positions just above the verumontanum, enucleating the median lobe, and then enucleating the lateral lobes.…”
Section: Methodsmentioning
confidence: 99%
“…In Turkey, a research team reported a morcellated prostate volume of 29.2 ± 11 ml [11], while another team reported that the resected adenoma volume was 52.3 ± 8.3 ml [29]. In South Korea, a sonographically calculated resected prostate tissue volume of 29.2 ± 20.1 ml [30] was reported in keeping with our observation that prostates we see in Nigeria or Africa presenting for surgery are much bigger than those seen in several other continents.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study found calculated enucleated volume was 26% higher than the postoperative specimen weight. 17 Therefore, the very small weight of 0.5g is unlikely to reflect the true amount of specimen enucleated.…”
Section: Discussionmentioning
confidence: 99%